The Creation of the “Sirena Varunya” in Presenting the Transformable Fashion Concept - Raharjanti, Aliyya; Kusumastuti, Adhi (Universitas Negeri Semarang, 2025)
The Sirena Varunya gown design was created as an exploration of transformable fashion design inspired by the dynamic visual of ocean waves while responding to sustainability issues in contemporary fashion. This study aims to produce a fashion design with high aesthetic value and optimal functionality. The research employed a practice-based research approach using the PPE development model (Planning, Production, Evaluation), which includes conceptual planning, production, and evaluation through a feasibility test conducted by three expert panellists. The feasibility test results indicate that the ‘Sirena Varunya’ design is in the “highly feasible” category, with an average score of 92% across six indicators: design, size, sewing technique, aesthetics, performance, and uniqueness. The uniqueness indicator received the highest score (98%), highlighting the originality and creative strength of the design. Nevertheless, the panellists provided several constructive recommendations, including strengthening beads embellishment attachment, improving the precision of the draping, adjusting the tail structure to prevent folding during movement, and exploring lighter materials to enhance comfort and mobility. Overall, the ‘Sirena Varunya’ design successfully translates ocean-inspired aesthetics into an innovative transformable fashion design while demonstrating strong creative identity and functional consideration.